Fundamental Concepts Of Bioinformatics - Krane, Dan E; Raymer,Michael L (Delhi Pearson, 2003)
This book is specifically designed to make bioinformatics accessible to undergraduates and prepare them for more advanced work. Students learn what programs are available for analyzing data, how to understand the basic algorithms that underlie these programs, what bioinformatic research is like, and other basic concepts. Information flows easily from one topic to the next, with enough detail to support the major concepts without overwhelming students.
Keywords: BIOINFORMATICS